Natura 2000 habitat mapping in Cyprus using high resolution orthophoto maps - Tzirkalli, Elli; Eliades, Elias; Chrysopolitou, Vasiliki; Hatziiordanou, Lena; Panagiotou, Nikos; Agapiou, Athos; Antoniou, Andreas; Xenophontos, Marina; Panayiotou, Charalampos; Hadjicharalambous, Helena (My University, 2018)
The Natura 2000 network is an essential tool for the protection and conservation of habitats and species throughout Europe. Each member state is responsible for the designation and management of Special Areas of Conservation (SACs), according to the provisions of the Habitats Directive (92/43/EEC). One of the key components for the conservation of these areas and their natural habitats is monitoring to ensure their long-term protection and maintenance. In this study, high resolution orthophotos were used to update the habitat maps of 17 SACs of the Natura 2000 network in Cyprus (areas under the effective control of the Government of the Republic of Cyprus) and also to map two (2) new candidate Sites of Community Importance (cSCIs). Habitat mapping involved an initial photo-interpretation using orthophotos and, subsequently, the aggregation of information from supplementary data (i.e. Corine Land Cover, crosswalks between EUNIS habitats Classification and Corine Land Cover, Google earth imagery from different years and seasons, etc.) to produce a map with all available information (spatial and descriptive) regarding habitat types and their cover area. Validation of the updated habitat mapping was performed by habitat and flora experts, combined with extensive field work. Additionally, 100 monitoring protocols were used to record and assess the conservation degree of 13 different habitat types inside these 19 areas. The study demonstrates that high-resolution orthophotos, combined with field work, significantly contributed to the improvement of the Natura 2000 habitat mapping. Remote sensing applications are powerful tools for identifying, mapping and monitoring of the Natura 2000 habitats.
Keywords: Annex I habitat types; Habitat mapping; Natura 2000 network